Trends in Effort and Yield of Trawl Fisheries: A Case Study From the Mediterranean Sea - Russo, Tommaso; Carpentieri, Paolo; D’Andrea, Lorenzo; De Angelis, Paola; Fiorentino, Fabio; Franceschini, Simone; Garofalo, Germana; Labanchi, Lucio; Parisi, Antonio; Scardi, Michele; Cataudella, Stefano (Frontiers in Marine Science, 2019)
The rationale applied for monitoring and managing fisheries is based on the implicit assumption that yield and stocks status is essentially determined by fisheries. Moreover, the fisheries yield is quantified and analysed in terms of landings with respect to official management area of registration of vessels. In this way, the real area of activity of each fleet is not considered and this prevent an effective spatial analysis of the factors affecting fisheries yield and stocks status. This paper firstly presents a VMS-based reconstruction of the fishing effort and of the area of activity of the Italian trawlers in the Mediterranean Sea. The fishing area of each fleet is then used as a spatial reference to estimate primary productivity rate and gross primary production and to investigate, by using General Additive Models, the effects of trawling effort, primary production and time on fisheries yield, fisheries productivity and overexploitation rate for some key demersal species. The results evidence that the usage of satellite-based information of fishing activities and of primary production, when combined at the real spatial scale of fishing activities, could effectively improve our ability to analyse the response of the ecosystems to these driving forces and allow capturing the main trends of yield, productivity and overexploitation rate of demersal stocks.